Normative Data and Determinants of Macular, Disc, and Peripapillary Vascular Density in Healthy Myopic Children Using Optical Coherence Tomography Angiography - Chen, Ruru; Lian, Hengli; McAlinden, Colm; Skiadaresi, Eirini; Liu, Siyu; Wan, Ting; Diao, Kai; Pan, Hongxian; Qu, Jia; Huang, Jinhai; Li, Yiyu (Frontiers in Medicine, 2022)
Objective To establish a normative database for the vascular density (VD) in macular, disc, and peripapillary regions in healthy myopic children and to evaluate associated ocular features with optical coherence tomography angiography (OCTA). Methods This was an observational, prospective and cross-sectional study. 776 Chinese healthy myopic children (375 boys and 401 girls) were enrolled, mean (±SD) age 9.84 ± 1.98 (range 6–16) years. En-face angiogram OCTA was performed on 6 mm × 6 mm retinal and 4.5 mm × 4.5 mm disc regions. VD measurements in the macular retina were segmented into the four regions: superficial capillary plexus (SCP), intermediate capillary plexus (ICP), deep capillary plexus (DCP), and choriocapillaris (CC). Correlations between macular, disc, and peripapillary VD and possible influencing factors [age, gender, axial length (AL), spherical equivalent refraction (SER), right/left eye, and signal strength index (SSI)] were assessed by Pearson’s correlation and multivariate regression analysis. Results For macular scans, the corrected VD in the ICP region was (48.25 ± 4.24)% for the whole macular retina. The macular ICP VD in most sections was lower than the SCP, DCP, and CC (all P < 0.001). The corrected VD in CC was (72.96 ± 4.42)% for the whole macular retina. The macular CC VD in every section was all higher than the SCP, ICP, and DCP (all P < 0.001). The size of foveal avascular zone (FAZ) and foveal VD 300 (FD-300) was 0.28 mm2± 0.10 mm2 and (58.43 ± 4.17)% respectively. For disc scans, the corrected VD was (58.04 ± 2.73)% for the whole disc area. Both AL and SER were strongly correlated with ICP, DCP, and CC VD in all regions (all P < 0.01). Larger SSI was correlated with a lower VD in the SCP and ICP, and a higher VD in DCP and CC (all P < 0.01). Conclusion Vascular density values provide large scale normative data on macular, disc, and peripapillary vascular parameters in a large sample of healthy myopic children with OCTA measured in the four different retinal plexuses and regions. The VD in different regions had various influencing factors; mainly a close correlation with AL and SSI.